Bridging Success through Comparative: Uncovering the Motivation Potential of Improving Students' Writing, Individually vs Collaboratively - Azwinatul Hikmah; Muhammad Al Hafizh (Universitas Hamzanwadi, 2024)
Writing effectively is crucial in upper secondary education, yet many students face challenges with vocabulary, grammar, spelling, and punctuation. Educators can assist by incorporating both individual and collaborative writing methods. This study investigates the impact of these writing activities on students' writing skills and examines the role of student motivation. Using a causal-comparative method, the study involved 35 tenth-grade students from SMA Negeri 2 Tambang, Indonesia. A questionnaire based on Dörnyei (1994) indicators assessed student motivation levels, while a descriptive writing test evaluated their writing skills. Writing samples were scored using an analytical scoring rubric, and a two-way ANOVA analyzed the effects of motivation levels on writing skills in both individual and collaborative contexts. Results showed a significant interaction between the type of writing activity and motivation level, with a significance level of 0.006. The findings indicate that collaborative writing activities significantly enhance writing skills, while motivation levels do not have a substantial impact on writing performance. Educators are encouraged to blend individual and collaborative writing activities to optimize students' writing skill development. Individual writing supports personal reflection and growth, whereas collaborative writing promotes peer learning and idea exchange.